Complaints Speech Acts between Customer and Staff at Western Cafe - Putri, Ni Kadek Melia; Dian Puspita Candra, Komang (Humanis, 2024)
A complaint is an expression of dissatisfaction about an act, omission, decision, or service that expects of the feedback given by the user. This study focuses on an interaction between customer and server: Western Café In Canggu strongly conveys the interaction using speech act categories. The objective of this study is to ascertain the many classifications of speech acts employed within the context of interactions between restaurant customers and servers. The method and technique used to capture data for this study were qualitative analysis and note-taking. Furthermore, the data were analyzed by using theory: Searle’s theory of speech act (1969) and Austin (1962) is used to define and classify the categories of speech act  used  by the server and customer. The findings show from every interaction that guest and server made and expressing of directive and expressive. Directive point is the most common illocutionary act used in conversation that how make easier the hearer to understand what the speaker mean.